2021
DOI: 10.3389/fpsyg.2021.676376
|View full text |Cite
|
Sign up to set email alerts
|

Connection in Youth Development Key to the Mental Health Continuum in Ghana: A Structural Equation Model of Thriving and Flourishing Indicators

Abstract: Practitioners from sub-Saharan Africa are working to provide evidence-based intervention programs to address the mental health of established adults in poor rural communities in Ghana. However, institutions in Ghana also pursue youth policy for training human capital that can contribute to national development as a strategy to leverage its heavy demographic makeup of adolescents and emerging adults. Positive Youth Development (PYD) is a framework for measuring indicators of thriving for such youthful populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
(115 reference statements)
2
3
0
Order By: Relevance
“…The adequacy of the models created was supported by values of χ2/sd, RMSEA, SRMR, NNFI, CFI and IFI. These findings are consistent with previous studies conducted in diverse cultural contexts, such as China (Su et al, 2017), the Philippines (Buenconsejo et al, 2022), Ghana (Kabir et al, 2021), Spain (Gomez-Baya et al, 2021), Croatia (Gomez-Baya et al, 2022), Iceland (Gestsdottir et al, 2017), Norway (Holsen et al, 2016), Portugal (Tome et al, 2019), and Slovenia (Gonzalez et al, 2017), which have all reported that the 34-item Short Form of the scale showed sufficient data fit. Similarly, the 17-item Very Short Form has been found to have adequate construct validity for use in the Philippines (Buenconsejo et al, 2022), Hong Kong (Wong et al, 2021), and Iran (Babaee et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The adequacy of the models created was supported by values of χ2/sd, RMSEA, SRMR, NNFI, CFI and IFI. These findings are consistent with previous studies conducted in diverse cultural contexts, such as China (Su et al, 2017), the Philippines (Buenconsejo et al, 2022), Ghana (Kabir et al, 2021), Spain (Gomez-Baya et al, 2021), Croatia (Gomez-Baya et al, 2022), Iceland (Gestsdottir et al, 2017), Norway (Holsen et al, 2016), Portugal (Tome et al, 2019), and Slovenia (Gonzalez et al, 2017), which have all reported that the 34-item Short Form of the scale showed sufficient data fit. Similarly, the 17-item Very Short Form has been found to have adequate construct validity for use in the Philippines (Buenconsejo et al, 2022), Hong Kong (Wong et al, 2021), and Iran (Babaee et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…According to Alpar (2006), a correlation greater than .70 is recommended for test-retest evaluation, and above .60 is recommended for Cronbach Alpha, McDonald's Omega, and Combined reliability coefficients. The Short Form exhibited adequate reliability values in this study, with similar results found in other samples such as those from China (Su et al, 2017), the Philippines (Buenconsejo et al, 2022), Ghana (Kabir et al, 2021), Spain (Gomez-Baya et al, 2021), Croatia (Gomez-Baya et al, 2022, Malaysia (Abdul Kadir and Mohd, 2021), Portugal (Tome et al, 2019), and Slovenia (Gonzalez et al, 2017). However, the results of this study indicate that the Positive Youth Development Scale Very Short Form did not provide .60 (Alpar, 2006) of competence and character dimensions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Such an approach is considered an important element that helps young people stay away from risk factors related to dropping out of school, using alcohol, tobacco, and narcotic substances, engaging in criminal behavior as well as developing mental health issues at an early age (Kang et al, 2021;Sharma & Yukhymenko-Lescroart, 2022;Kozina et al, 2021;Mohamad, et al, 2021). Referring to numerous types of research, the findings suggest that the 5Cs have a positive impact on the development of young people and on incrtheiring their quality of life, general well-being, and mental health (Ferrer-Wreder et al, 2021;Årdal, et al, 2018;Kabir, Doku & Wiium, 2021).…”
Section: The 5cs As a Dimension Of The Pyd Modelmentioning
confidence: 99%
“…Life Purpose acts as a protective factor in relation to the components of the 5Cs and general well-being (Abdul Kadir & Mohd, 2021). In addition, it has an important role in developing the 5Cs during the process of personal growth and the transformation of young people into mentally mature adults capable of responding effectively to all life's challenges (Kabir, Doku, & Wiium, 2021;Bøhlerengen, & Wiium, 2022).…”
Section: Introductionmentioning
confidence: 99%